2002
DOI: 10.1080/10803548.2002.11076520
|View full text |Cite
|
Sign up to set email alerts
|

The Cytotoxicity of Some Organic Solvents on Isolated Hepatocytes in Monolayer Culture

Abstract: The cytotoxic effects of volatile and water-insoluble organic solvents (ethylbenzene, tetrachloroethylene, n-hexane) were tested on isolated hepatocytes in monolayer culture by using the 3-(4,5 dimethylthiazol-2-yl)-2,5 diphenyltetrazolium bromide (MTT) reduction assay. All of the tested compounds inhibited metabolic activity of hepatocytes and this effect depended on the concentration of solvents in the incubatory medium. The presence of fetal calf serum in the medium did not change the cytotoxicity of xenobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 10 publications
(4 reference statements)
0
10
0
Order By: Relevance
“…MTT test, supported by a strong body of literature, is a metabolic activity assay which involves the use of tetrazolium salt cleaved in the mitochondria of metabolically active cells to colored formazan salt that can be measured by absorbance. The amount of formazan dye produced is directly proportional to the quantity of metabolically active cells [4951]. …”
Section: Discussionmentioning
confidence: 99%
“…MTT test, supported by a strong body of literature, is a metabolic activity assay which involves the use of tetrazolium salt cleaved in the mitochondria of metabolically active cells to colored formazan salt that can be measured by absorbance. The amount of formazan dye produced is directly proportional to the quantity of metabolically active cells [4951]. …”
Section: Discussionmentioning
confidence: 99%
“…Since many of these compounds are waterinsoluble, the use of organic solvent is necessary (4). However, a common concern when introducing organic solvents to the growth medium is toxic effects of the solvent on cells (2,5,8,9). In addition, using unsuitable solvents might cause the loss of biological activities in compounds; therefore, it may seriously affect the outcome of the experiment (1, 3).…”
Section: Discussionmentioning
confidence: 99%
“…Some of the commonly used organic solvents such as acetone (Log P, -0.24), ethanol (Log P, -0.31), dimethyl sulfoxide (DMSO) (Log P, -1.35) and dimethyl formamide (DMF) (Log P, -1.01) were selected in the current study. Based on reports from in vitro studies, possible toxic effects of these organic solvents are expected (5)(6)(7). Several authors have reported interference of frequently used solvents with cellular based assays (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…For the assessment of acute effects of thinner treatment on neuronal cells and the evaluation of the dose-and time-response dependencies, we added different concentration of thinner (0.0%, 0.2%, 0.4% and 0.8%) to the culture medium for different time of incubation (1h, 6h and 24h). In order to improve the solubility of thinner compounds and therefore facilitate their absorption by the cells, the tested mixture was dissolved directly in culture medium with fetal bovine serum (10%) [30]. In fact, to dissolve thinner, we have avoided the use in our experiments DMSO or alcohol in order to prevent the cytotoxic action of these compounds [31,32,33].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, to dissolve thinner, we have avoided the use in our experiments DMSO or alcohol in order to prevent the cytotoxic action of these compounds [31,32,33]. It should be pointed out that during the current protocol we used a free mineral oil medium, since it has been proven that this oil could dramatically affect neurons and astrocytes viability because of their intense metabolism [30]. Interestingly, cytotoxic potential of the tested solvent cannot be disrupted following the addition of fetal bovine serum to cell culture medium.…”
Section: Discussionmentioning
confidence: 99%